(untitled) (Journal of Human Sciences, 2020)
This research addresses the most significant semantic issues in the-book ofThimar AL-kuloub by AlThaalbi, such as the idea of ​​semantic fields, the context of the situation, the question of Collocation, as well as the issue of semantic transformation, and the semiology of topic. Contemporary reflects the extent of the contribution made by Thaalbi in semantic research. The research problem lies in a central question: Are there any semantic practices in the book of Thimar ALkuloub that are close to modern semantic theories? The research section includes an introduction, five demands and a conclusion.